2021
DOI: 10.1177/20552076211019250
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of teledentistry in detecting tooth erosion in patients with eating disorders

Abstract: Objective The aim of this study was to demonstrate that including a teledentistry consultation in the standard care provided to patients in an eating disorder day hospital could be beneficial, notably for screening for particular pathologies and preventing dental erosion. Methods We included 50 patients from the eating disorders unit of the University Hospital of Montpellier, all of whom underwent a dental examination using asynchronous telemedicine. We recorded the data using teledentistry software for the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
0
12
1
Order By: Relevance
“…Reported asking about physical health and referring but not mental health and rarely referred to mental health provider. Did not feel prepared to communicate with patients and health care providers from other disciplines about mental health Galindo [ 31 ] USA To describe the reconstruction of a maxillary anterior segment using immediate implant placement and immediate implant loading techniques, aided by computer- guided implant treatment software and stereolithographic models and surgical templates, in a patient with a history of ED Case study N = 1 BN This clinical report describes rehabilitation using implant- supported FPDs on immediately placed and immediately loaded dental implants, aided by computer-guided implant treatment software, stereolithographic models, and surgical templates, of a partially dentate patient affected by EDs Giraudeau [ 32 ] France To assess the benefits and feasibility of providing a systematic dental examination via telemedicine for all patients in the ED day hospital Two phase study: virtual visit and analysis N = 50 AN, BN Dental erosion was found in 92% of the patients, and 50% had at least one tooth with a BEWE score of 2 or 3 Hermont [ 41 ] Brazil To compare the occurrence of tooth erosion and dental caries in adolescents with and without risk behavior for EDs Controlled cross-sectional study N = 1,203 N/A Severe risk behavior for EDs was significantly associated with tooth erosion, but not with dental caries Imai [ 42 ] Japan To present a case of necrotizing sialometaplasia (NS) accompanied by significant dental erosion of the maxillary teeth of the palatal surfaces owing to chronic self-induced vomiting Case study N = 1 N/A Temporary worsening of binging-purging before the development of NS would likely have led to an increase in traumatic stress and chemical exposure of the palate. Iron deficiency hypochromic anemia could compromise the steady supply of oxygen to the palate locally affected by frequent abnormal eating behaviors.…”
Section: Resultsmentioning
confidence: 99%
“…Reported asking about physical health and referring but not mental health and rarely referred to mental health provider. Did not feel prepared to communicate with patients and health care providers from other disciplines about mental health Galindo [ 31 ] USA To describe the reconstruction of a maxillary anterior segment using immediate implant placement and immediate implant loading techniques, aided by computer- guided implant treatment software and stereolithographic models and surgical templates, in a patient with a history of ED Case study N = 1 BN This clinical report describes rehabilitation using implant- supported FPDs on immediately placed and immediately loaded dental implants, aided by computer-guided implant treatment software, stereolithographic models, and surgical templates, of a partially dentate patient affected by EDs Giraudeau [ 32 ] France To assess the benefits and feasibility of providing a systematic dental examination via telemedicine for all patients in the ED day hospital Two phase study: virtual visit and analysis N = 50 AN, BN Dental erosion was found in 92% of the patients, and 50% had at least one tooth with a BEWE score of 2 or 3 Hermont [ 41 ] Brazil To compare the occurrence of tooth erosion and dental caries in adolescents with and without risk behavior for EDs Controlled cross-sectional study N = 1,203 N/A Severe risk behavior for EDs was significantly associated with tooth erosion, but not with dental caries Imai [ 42 ] Japan To present a case of necrotizing sialometaplasia (NS) accompanied by significant dental erosion of the maxillary teeth of the palatal surfaces owing to chronic self-induced vomiting Case study N = 1 N/A Temporary worsening of binging-purging before the development of NS would likely have led to an increase in traumatic stress and chemical exposure of the palate. Iron deficiency hypochromic anemia could compromise the steady supply of oxygen to the palate locally affected by frequent abnormal eating behaviors.…”
Section: Resultsmentioning
confidence: 99%
“…Each arch was divided into three sextants. The total BEWE index, ranging from 0–18, was obtained from the sum of the highest score for each sextant [ 10 , 11 ]. The dental caries status of each patient was scored according to the Decayed, Missing and Filled Teeth (DMFT) index.…”
Section: Methodsmentioning
confidence: 99%
“…A recent research at Newcastle Dental Hospital's Paediatric Dentistry New Patient Service has shown that TD may be employed in many steps of pediatric dentistry, including initial triage, remote assessment, reinforcement of prevention, implementing initial management, and building rapport, with maximum safety and minimal inconvenience for both child and parents [ 22 ]. Several other works show that TD consultation inserted into the standard day hospital protocol provided to patients with eating disorders is convenient, more so for particular pathologies’ screening and for dental erosion prevention [ 23 ].…”
Section: Current Data On Teledentistrymentioning
confidence: 99%